EAST/SeSAME Syndrome and Beyond: The Spectrum of Kir4.1- and Kir5.1-Associated Channelopathies - Lo, Jacky; Forst, Anna-Lena; Warth, Richard; Zdebik, Anselm A. (Frontiers in Physiology, 2022)
In 2009, two groups independently linked human mutations in the inwardly rectifying K+ channel Kir4.1 (gene name KCNJ10) to a syndrome affecting the central nervous system (CNS), hearing, and renal tubular salt reabsorption. The autosomal recessive syndrome has been named EAST (epilepsy, ataxia, sensorineural deafness, and renal tubulopathy) or SeSAME syndrome (seizures, sensorineural deafness, ataxia, intellectual disability, and electrolyte imbalance), accordingly. Renal dysfunction in EAST/SeSAME patients results in loss of Na+, K+, and Mg2+ with urine, activation of the renin-angiotensin-aldosterone system, and hypokalemic metabolic alkalosis. Kir4.1 is highly expressed in affected organs: the CNS, inner ear, and kidney. In the kidney, it mostly forms heteromeric channels with Kir5.1 (KCNJ16). Biallelic loss of function mutations of Kir5.1 can also have disease significance, but the clinical symptoms differ substantially from those of EAST/SeSAME syndrome: although sensorineural hearing loss and hypokalemia are replicated, there is no alkalosis, but rather acidosis of variable severity; in contrast to EAST/SeSAME syndrome, the CNS is unaffected. This review provides a framework for understanding some of these differences, and will guide the reader through the growing literature on Kir4.1 and Kir5.1, discussing the complex disease mechanisms and the variable expression of disease symptoms from a molecular and systems physiology perspective. Knowledge of the pathophysiology of these diseases and their multifaceted clinical spectrum is an important prerequisite for making the correct diagnosis and forms the basis for personalized therapies.